(untitled) (REMUNOM, 2024)
This study investigates the impact of inadequate fruit consumption, especially in individuals with pre-existing metabolic conditions, focusing on its health implications with an emphasis on possible nursing interventions. The analysis addresses fruit consumption patterns and their direct relationship with glycemic control, seeking to understand the underlying mechanisms of this complex interaction. The relevance of this study lies in the need for a holistic approach to health promotion that recognizes not only the benefits but also the risks associated with certain dietary behaviors. Understanding fruit intake patterns and their influence on glycemic control is crucial for developing effective intervention strategies, particularly in vulnerable populations.